KEPATUHAN WAJIB PAJAK UMKM BATIK KABUPATEN BANTUL - Pratomo, Sigit Adhi; Amelia, Rizky Windar; Sulistyowatie, Syska Lady (Widya Dharma Journal of Business - WIJoB, 2023)
SMEs are businesses that can still run in the midst of a crisis. The classic problem that often arises is the low level of tax payment by SMEs. So with PP No. 23 of 2018 which took effect on July 1, 2018 where the government reduced the final tax rate for SMEs from 1% to 0.5%, it is hoped that it will be able to increase taxpayer awareness to comply with paying taxes. In this study, the factors taken are Taxation Socialization, Fiscal Services, and Implementation of the Self Assessment System. This research was conducted on batik SMEs taxpayers in Bantul Regency, the purpose of this study was to determine how much influence the level of Tax Socialization, Fiscal Services, and Implementation of the Self Assessment System on taxpayer compliance. The population is SMEs batik taxpayers in Bantul Regency. The results of the study are 1) that the results of the F test simultaneously the variables of taxation socialization, Fiscal Services and Implementation of the Self Assessment System have a positive effect on taxpayer compliance. 2) The results of the t test partially the three variables of tax socialization, Fiscal Services and Implementation of the Self Assessment System have a positive effect on taxpayer compliance. Keywords: SMEs, Tax Compliance, SMEs Tax.